Learning Trends of Medical Students in a Private Sector University (Medical Forum Monthly, 2024)
Objective: Identify various learning trends to collect data on computer use and its timing to analyze learning patterns in hostels and day scholars.Study Design: Analytic study.Place and Duration of Study: This study was conducted at the Department of Community Medicine, Isra University, Hyderabad from January to December 2017.Materials and Methods: A questionnaire detailing on learning trends was distributed in 3rd year MBBS students.Results: A total of 89 students participated in the study including male as 40.4% and females as 59.6%. Western books were liked by 7 (7.94%) students while 92.08 liked Pakistani and non-western books. and regarding their academic performance 38.20% scored high while 61.79% showed either medium or lower performance.Conclusion: Our study concludes that students are a user of many learning resources like computer and internet, library text books, but it is not clear high use of computer internet will leads to high performance in final results of examination.